Skin and Gut Microbiome in Psoriasis: Gaining Insight Into the Pathophysiology of It and Finding Novel Therapeutic Strategies - Chen, Lihui; Li, Jie; Zhu, Wu; Kuang, Yehong; Liu, Tao; Zhang, Wei; Chen, Xiang; Peng, Cong (Frontiers in Microbiology, 2020)
Psoriasis affects the health of myriad populations around the world. The pathogenesis is multifactorial, and the exact driving factor remains unclear. This condition arises from the interaction between hyperproliferative keratinocytes and infiltrating immune cells, with poor prognosis and high recurrence. Better clinical treatments remain to be explored. There is much evidence that alterations in the skin and intestinal microbiome play an important role in the pathogenesis of psoriasis, and restoration of the microbiome is a promising preventive and therapeutic strategy for psoriasis. Herein, we have reviewed recent studies on the psoriasis-related microbiome in an attempt to confidently identify the “core” microbiome of psoriasis patients, understand the role of microorganisms in the pathogenesis of psoriasis, and explore new therapeutic strategies for psoriasis through microbial intervention.